Toward creative physics learning: need analysis of PjBL-based physics modules with deep learning - Fadilla Septiani; Ratnawulan Ratnawulan; Fatni Mufit; Emiliannur Emiliannur (Global Econedu, 2026)
This study aimed to analyze the need for developing a Project Based Learning (PjBL)-based physics module integrated with the Deep Learning approach to enhance students' creative thinking skills on the topic of climate change. A descriptive quantitative survey was conducted as the analysis phase of the ADDIE development model. The participants were physics teachers and Grade X students at SMA Negeri 5 Payakumbuh, selected through purposive sampling. Data were collected using classroom observations, semi-structured interviews, needs assessment questionnaires, and a creative thinking skills assessment. The data were analyzed descriptively using percentages and qualitative interpretation. The findings showed that physics instruction still relied on conventional teaching materials and teacher-centered practices, limiting students' opportunities to develop creative thinking skills. The needs assessment indicated that both teachers and students required a physics module integrating PjBL and the Deep Learning approach to support meaningful and contextual learning. Furthermore, students' creative thinking skills remained relatively low across the four dimensions of fluency, flexibility, originality, and elaboration. These findings provide empirical evidence supporting the development of an innovative physics module aligned with the Merdeka Curriculum to improve students' creative thinking skills and promote more active, student-centered learning on climate change